Robert Adlington, Composing Dissent. Avant-Garde Music in 1960s Amsterdam - Delpeut, Thomas (BMGN - Low Countries Historical Review, 2017)
Robert Adlington, Composing Dissent. Avant-Garde Music in 1960s Amsterdam (New York: Oxford University Press, 2013, 384 pp., isbn 978 0 19 998101 4).